Development of internship placement web based system / Asilatuz Zakiah Muhamad - Muhamad, Asilatuz Zakiah (2018)
The internship program is the program that involve student, lecture, and coordinator to get the need of completing the degree by finishing the internship program. Internship placement occurs during last semester where student must take this program for them graduated. The current process are using the manual system that coordinator have manually allocate the lecture and student for the internship program. Therefore, objective for this project are to identify user requirement of Internship Placement Web-Based System, to design the Internship Placement Web-Based System and to develop Internship Placement Web-Based System for FSKM. The scope of this study will be design an internship web-based system for coordinator, internship supervisor and internship student of Faculty of Computer & Mathematical Sciences, UiTM Shah Alam. The method for the problem is interviewing with the coordinator, Prof Madya Rashidah Rawi to get the requirement needed and problem in Internship of FSKM. Through the analysis of the requirements, the design of the interface prototype was done after implemented the web based system assessment and created a storyboards as an early design approach. Then, the prototype underwent evaluation by coordinator through the interview. The evaluation results have led to the improvement of the prototype to produce final design of the web based system user interface. This project will help the coordinator manage internship placement for the supervisor and student more systematic.